Tindak Tutur Ekspresif pada Film Perayaan Mati Rasa Sutradara Umay Shahab - Raihani Maulida; Herlinda Putri; Sandi Saputra (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This research aims to describe the forms and functions of expressive speech acts found in the film “Perayaan Mati Rasa” by Umay Shahab. This film was chosen because it showcases various forms of emotional expression that reflect the reality of everyday communication. The method used is descriptive qualitative. The data, consisting of the characters' utterances in the film, were collected thru observation and note-taking techniques, then analyzed using Chaer's theory of speech acts. The research results indicate that there are six types of expressive speech acts in this film: expressing gratitude, apologizing, praising, showing sympathy, expressing anger/disappointment, and praying/hoping. Each type of speech act has a different social function, such as building emotional closeness, improving social relationships, expressing empathy, and affirming moral values in interactions between characters. This finding suggests that the film “Perayaan Mati Rasa” not only represents emotional conflict but also depicts the dynamics of human communication laden with social and psychological values. The results of this research are expected to serve as a reference in pragmatic studies and discourse analysis, particularly in the analysis of expressive speech acts in literary works or film media.